Association of Different Biochemical and Hemodynamic Characteristic with Type 2 Diabetes Mellitus and Hypertension in Nephrolithiasis Patients - Katwal, BM; Gautam, N; Shrestha, S; Adhikari, R; Baral, H; Jha, SK; Jha, G (Kathmandu University Medical Journal, 2023)
Background Although Nephrolithiasis is a common condition caused by a wide variety of metabolic or environmental disturbances, its being one of the major factor of morbidity. Incidence of kidney stone disease (KSD) is highly affected by metabolic disorders and change in blood pressure and glucose. Objective To find out association of different biochemical and hemodynamic parameters with various glycemic status and hypertension in kidney stone disease. Method A cross sectional study was conducted in patients diagnosed as nephrolithiasis by using re¬nal ultrasonography and underwent nephrectomy between January 2019 to January 2021 in Shahid Dharmabhakta National Transplant Centre (SDNTC). A total of 100 subjects with 60 male and 40 females were enrolled. Glycemic status was categorized based on criteria of American Diabetes Association (ADA) and hypertension was defined as BP ≥ 140/90 mm Hg in right arm supine position. All biochemical and hemodynamic profile was carried out following standard protocol. Result Out of 100 patients enrolled, pre-diabetes accounted for 31% followed by diabetes (4%). However, hypertension comprised of 66% in total subjects. Serum urea, cholesterol and triglyceride level were found to be increased by 84.6%, 67.7% and 64.7% respectively in diabetes followed by increase of 3.9%, 19.5% and 3.1% respectively in prediabetes when compared to normal glycemic condition in nephrolithiasis subjects. Serum fasting blood glucose, creatinine and uric acid level was observed significantly higher (p=0.003, p=0.004, p < 0.001 respectively) in hypertensive patients. Duration of hospital stay was also seen positively correlated with hypertension. Conclusion Not only diabetes, prediabetes also manifests the increased risk of kidney stone disease along with hypertension. There is significant impairment in renal function and lipid profile based on diabetes mellitus and hypertension. Early identifying these systemic diseases, different biochemical and hemodynamic parameters and proper treatment accordingly may minimize risk and prevent serious complication in these patients.